Empowering Future Professionals: A Project-Based Learning and Positive Psychology Model for Academic Writing in an EFL Context - Sakkir, Geminastiti; Nur, Sahril; Sahril Nurfadhilah, Auliyanti (Celebes Journal of Language Studies, 2025)
Academic writing is a cornerstone of higher education, yet for English as a Foreign Language (EFL) students, it presents significant challenges related to linguistic competence, genre mastery, and writing anxiety. This study investigates the impact of a novel pedagogical model integrating Project-Based Learning (PjBL) and Positive Psychology (PP) on multiple dimensions of student engagement. The study was conducted within a compulsory "Academic Writing for Professionals" course for English Literature students at Universitas Negeri Makassar (UNM). Employing a mixed-methods, quasi-experimental design with 65 third-year students, the intervention group (n=33) engaged with the PjBL-PP model, while a comparison group (n=32) followed a traditional curriculum. Data were collected via pre- and post-tests measuring academic writing self-efficacy, writing apprehension, and a multi-dimensional student engagement scale (cognitive, behavioral, emotional). Qualitative data from project portfolios and semi-structured interviews were used to explore these dimensions and the concept of social presence. ANCOVA results showed the intervention group demonstrated significantly higher cognitive, behavioral, and emotional engagement, and higher self-efficacy (p < .001), alongside a significant reduction in writing apprehension (p < .001). Qualitative analysis revealed how the model fostered deep cognitive processing through authentic tasks, promoted sustained behavioral effort, created a positive emotional climate, and established a strong sense of social presence. This study provides a robust framework for transforming academic writing instruction, demonstrating that the synergy of PjBL and PP cultivates the holistic engagement necessary for EFL students to become confident and competent professional writers.